EFIKASI EKSTRAK DAUN ZODIA (Evodia suaveolens) PELARUT HEKSANA DALAM MEMATIKAN LARVA INSTAR III Aedes aegypti - Setiyadi, Didi; Martini, Martini; Hadi, Mochamad (Universitas Tribhuwana Tunggadewi, 2020)
DHF is a disease caused by a virus which is transmitted through the bite of the Aedes aegypti mosquito and is one of the health problems in Indonesia. Efforts to decide the transmission of DHF by controlling the population of Aedes aegypti at the larval stage using larvaside temepos. Long-term use of temephos causes Aedes aegypti resistance and environmental damage. One of the plants that has the potential as botanical larvaside is the leaves of zodia (Evodia suaveolens). The purpose of this study was to prove the efficacy of zodia leaves of hexane solvent for killing A. aegypti larvae. This type of research is a pure experiment with the post test only control group design. The research sample is A. aegypti stage III susceptible strain. There are 7 groups consisting of 1 negative control (aquades), positive control (1 ppm temepos) and 5 treatment groups (zodia leaf extract). Data on larval mortality were counted 24 hours after treatment. The results of the one way ANOVA test showed that there were differences in mortality between test groups with a p value: 0.001 α (0.05). Zodia leaf extract probit test results showed LC50-24 hour and LC90-24 hour values of 0,443 ppm and 0,788 ppm. Zodia leaf extract with hexane solvent has efficacy as Aedes aegypti larvicide.